Zarzou Beauty / Nurulhuda Ainaa Ramli - Ramli, Nurulhuda Ainaa (2021)
Zarzou Beauty is the brand of serum that usually people use as one of daily routine skincare. This serum was established on the 1st of July 2019. Next, this product had been created by the founder while trying ACCA. She found the lovely ingredient product toward skincare that will give the greatest joy and being an avid skincare freak. This product also really affordable and the price are suitable for the function of serum. The target market of this serum is teenagers, adults either man or woman. The founder saw a problem in which people must purchase a variety of serums to solve their problems, however this product can help people solve their skin problems with just one product. The Brightening, Hydrating Facial Serum was the first product they released. However, the product's recipe is safe to use, and it differs from that of other local products. I learned how to increase my sales and share the best serum ever through social media. At the same time, I'm able to tell the difference between a hard and a soft sell. Last but not least, I learned how to use the G0-Ecommerce Website to find out how to record and monitor sales every month. It teaches me how to advertise and learn more about marketing and marketing strategy as a result of this.